2016
DOI: 10.1016/j.jpurol.2015.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of the clinical and urodynamic outcomes of secondary tethered spinal cord before and after spinal cord untethering

Abstract: Patients with secondary TSC are expected to have progression of their symptoms over time if not untethered. From here comes the importance of closely performing clinical/UDS evaluation to pick-up changes early before they progress. Surprisingly, clinical outcomes after SCU with detailed description of the auxiliary management are sparse in the literature. Most studies focus on UDS outcomes. We provided in the current study a detailed discussion of the clinical outcomes, auxiliary-managements used to achieve co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…26,27 This was indicated to be the underlying reason in a recent report. 28 In addition, the current study would like to highlight the benefit of early detection by multidisciplinary collaboration. Thus, the reason that 88% of patients had urological deterioration may be attributable to the active participation of urologists in diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 This was indicated to be the underlying reason in a recent report. 28 In addition, the current study would like to highlight the benefit of early detection by multidisciplinary collaboration. Thus, the reason that 88% of patients had urological deterioration may be attributable to the active participation of urologists in diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary TSC occurs in 3–30% of patients with a history of spinal cord dysraphism repair. The symptoms of TSC include back pain, leg weakness, foot deformity, and lower urinary tract dysfunction such as urinary incontinence or retention [ 6 ]. It is often difficult to diagnose secondary TSC in patients with a prior history of spinal cord dysraphism repair, especially if neurological symptoms are not evident and there is no typical urological dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Urodynamic evaluations are important for diagnosis and subsequent management, because the urinary symptoms and urodynamic parameters may not always match [ 7 ]. Although several reports [ 6 , 8 ] have noted that lower urinary tract symptoms and urodynamic parameters improve by untethering surgery for secondary TSC, these were retrospective studies with a small number of patients, and some patients had inadequate improvement in low bladder compliance on UDS; thus, the level of evidence can be considered weak. The patient in the current report is in follow-up with the neurosurgeon and undergoes synsacrum MRI scans regularly; however, she and her parents have declined untethering surgery, as she has no symptoms, and untethering surgery is not a riskless procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative detrusor overactivity, which was considered to be the most significant indicator for the early diagnosis of retethering, was improved by 75% after surgery. According to Alzahrani et al 4) , UDS parameters that revealed postoperative improvement most were intravesical pressure at total cystometric bladder capacity and bladder compliance.…”
Section: Bladder Functionmentioning
confidence: 99%